Electroconductive Photo-Curable PEGDA-Gelatin/PEDOT:PSS Hydrogels for Prospective Cardiac Tissue Engineering Application - Testore, Daniele; Zoso, Alice; Kortaberria, Galder; Sangermano, Marco; Chiono, Valeria (Frontiers in Bioengineering and Biotechnology, 2022)
Electroconductive hydrogels (ECHs) have attracted interest for tissue engineering applications due to their ability to promote the regeneration of electroactive tissues. Hence, ECHs with tunable electrical and mechanical properties, bioactivity, biocompatibility and biodegradability are demanded. In this work, ECHs based on photo-crosslinked blends of polyethylene glycol diacrylate (PEGDA) and gelatin with different PEGDA:gelatin ratios (1:1, 1.5:1 and 2:1 wt./wt.), and containing poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) (0.0, 0.1, 0,3 and 0.5% w/v%) were prepared. Main novelty was the use of gelatin as bioactive component and co-initiator in the photo-crosslinking process, leading to its successful incorporation in the hydrogel network. Physical properties could be modulated by the initial PEGDA:gelatin weight ratio. Pristine hydrogels with increasing PEGDA:gelatin ratio showed: (i) an increasing compressive elastic modulus from 5 to 28 kPa; (ii) a decreasing weight loss from 62% to 43% after 2 weeks incubation in phosphate buffered saline at 37°C; (iii) reduced crosslinking time; (iv) higher crosslinking density and (v) lower water absorption. The addition of PEDOT:PSS in the hydrogels reduced photo-crosslinking time (from 60 to 10 s) increasing their surface and bulk electrical properties. Finally, in vitro tests with human cardiac fibroblasts showed that hydrogels were cytocompatible and samples with 1.5:1 initial PEGDA:gelatin ratio promoted the highest cell adhesion at 24 h. Results from this work suggested the potential of electroconductive photo-curable PEGDA-gelatin/PEDOT:PSS hydrogels for prospective cardiac tissue engineering applications.